The pests of a pest: A systematic review of ectoparasitic fauna among synanthropic rodents in the 21st century with meta-analysis - Jeffery Ho (2022)
Synanthropic rodents are important urban pests that frequently carry hematophagous ectoparasites. These blood-sucking pests are capable of transmitting epizootic and zoonotic pathogens by landing on one host after feeding on an infected animal. This study aimed to estimate the prevalence of ectoparasites carried by synanthropic rodents and discuss the pathogens that are associated with these external parasites. We searched relevant literatures using predefined criteria in the following databases: EMBASE, PUBMED, Web of Science and Scopus from January 2000 to June 2020. Quality of studies was evaluated using Newcastle-Ottawa scale (NOS). Of 35 included studies from 15 countries in Africa, America, Asia, Europe and Oceania, black rats (R. rattus), brown rats (R. norvegicus), pacific rats (R. exulans) and house mice (Mus musculus) were common synanthropic rodents. Mites (Mesostigmata, Sarcoptiformes and Trombidiformes) were the most prevalent (42.6%, 95% CI 26–59.2), followed by ticks (Ixodida) (21.5%, 95% CI 10.5–32.6), lice (Phthiraptera) (17.8%, 95% CI 7.7–27.9) and fleas (Siphonaptera) (14.1%, 95% CI 10.1–18.1). Heterogeneity (I2>96%) across studies was statistically significant. The ectoparasitic fauna was shared considerably by different urban rodent species and appeared to be more diverse in R. rattus and R. norvegicus. Nonetheless, pathogens carried by these ectoparasites were rarely investigated. In conclusion, ectoparasites are ubiquitous in urban-dwelling rodents but our understanding of the epidemiology and the associated pathogens of these parasites remains limited. Further studies are warranted to unravel the pathogen landscape found in rodent-associated ectoparasites.